PENGARUH KOMPENSASI DAN PENEMPATAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. MANDIRI TUNAS FINANCE CABANG BENGKULU - Rahmat Gunawan; Onsardi Onsardi (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2020)
This study aims to determine the effect of compensation and work placement on employee performance at PT. Mandiri Tunas Finance Bengkulu Branch, both partially and simultaneously. There are several factors that will be discussed in this study, including Compensation (X1), and Work Placement (X2). The object of this research is 50 employees at PT. Mandiri Tunas Finance Bengkulu Branch. In this research the authors use the method of data collection by means of observation, questionnaires or questionnaires, and interviews.There are several data analysis techniques used in this study, including using the instrument test, classic assumption test, respondent response analysis, multiple linear regression analysis, determinant coefficient, and also hypothesis testing. From the results of tests that have been carried out it can be concluded that the compensation variable (X1), and work placement (X2) have a partial or simultaneous effect on employee performance at PT. Mandiri Tunas Finance Bengkulu Branch. From the results of multiple linear regression tests obtained the regression equation is as follows: Y = 4.101 + 0.978 (X1) + 0.640 (X2). Keywords: Compensation, Work Placement and Employee Performance.